The evidence mapping of wasting programmes and their impact along the continuum of care for wasting in low- and middle-income countries: A rapid review protocol - Verstraeten, Roosmarijn; Touré, Mariama; Diatta, Dieynab; Huybregts, Lieven; Booth, Andrew; Becquey, Elodie (International Food Policy Research Institute, 2021)
The Transform Nutrition West Africa project is a regional platform that aims to improve and support and program decisions and actions to accelerate reductions in maternal and child undernutrition through an inclusive process of knowledge generation and mobilization. Recognizing that knowledge is derived from evidence and experience, TNWA takes a ‘knowledge for action’ approach. As such, TNWA focuses on strengthening the latter stages of the data value chain (namely analysis, translation, and dissemination for decision-making). Through a regional consultation with different stakeholders (researchers, NGOs, civil society, private sector, government, UN, donor agencies) from various sectors, key priorities for future action in the region were identified. These included capturing, documenting, and learning from implementation experiences, and accelerating equitable program coverage of mother, infant and young child interventions at scale. We apply evidence synthesis approaches (i.e., rapid reviews) to identify best practices on topics as prioritized by regional stakeholders. Previous topics include effectiveness and implementation experience of interventions to improve exclusive breastfeeding and early initiation of breastfeeding in low- and middle-income countries (LMICs), implementation tools for nutrition, and a landscape analysis of research on adolescent nutrition in the region. Through engagements with UNICEF, the Regional Nutrition Working Group (which is a collective of donors, INGO’s, researchers, development agencies that are active in nutrition in the region), and other stakeholders, the next topic identified as a key issue for the region was wasting among children under five years of age. The output of this rapid review will not only inform various stakeholders active in the region but will also support the Integrated Research on Acute Malnutrition in the Sahel project (IRAM). IRAM aims to generate evidence on wasting prevention and treatment interventions in four countries: Chad, Mauritania, Mali and Niger (multi-country partnership between UNICEF and IFPRI). Stakeholders (review users, such as implementers and researchers) will be involved throughout. They will be consulted to set and refine the review question, eligibility criteria, and the outcome of interest. Consultations will ensure that this rapid review is fit for purpose.